Answer:
16 v^3 w^7
Step-by-step explanation:
Simplify the following:
4 v^3 w (-2 w^3)^2
Hint: | Distribute exponents over products in (-2 w^3)^2.
Multiply each exponent in -2 w^3 by 2:
4 v^3 w×(-2)^2 w^(2×3)
Hint: | Multiply 2 and 3 together.
2×3 = 6:
4×(-2)^2 v^3 w w^6
Hint: | Evaluate (-2)^2.
(-2)^2 = 4:
4×4 v^3 w w^6
Hint: | Combine products of like terms.
4 v^3 w×4 w^6 = 4×4 v^3 w^(1 + 6):
4×4 v^3 w^(1 + 6)
Hint: | Evaluate 1 + 6.
1 + 6 = 7:
4×4 v^3 w^7
Hint: | Multiply 4 and 4 together.
4×4 = 16:
Answer: 16 v^3 w^7